Rare bird documentation form for Greater Scaup at Coralville Reservoir, 1986 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1986)
Rare bird documentation form for a Greater Scaup at Coralville Reservoir in Johnson County, IA on March 23, 1986. Epson - sheet feed